Investigation into the protective ability of monovalent and bivalent A Malaysia 97 and A22 Iraq 64 vaccine strains against infection with an A/Asia/SEA-97 variant in pigs - Horsington, Jacquelyn; Singanallur Balasubramanian, Nagendrakumar; Nfon, Charles K.; Bittner, Hilary; Vosloo, Wilna (Frontiers in Veterinary Science, 2022)
Over the last 15 years, FMDV serotype A viruses in South-East Asia (A/ASIA/SEA-97 lineage) have diverged into several clusters. Variants from Thailand in 2011-2013 have caused vaccine failures and returned poor r1-values (<0.30) to A22 Iraq 64 (A22) and A Malaysia 97 (A May) vaccine strains. We investigated the protective ability of monovalent and bivalent A Malaysia 97 and A22 Iraq 64 vaccine strains against infection with an A/Asia/SEA-97 variant in pigs. Pigs were challenged with a variant of A/Asia/SEA-97 lineage either 21- or 7- days post-vaccination (V21 or V7) using the heal-bulb challenge. Only one in five pigs were protected in the V21 monovalent vaccine groups. Less severe clinical signs were observed in the A22 IRQ group compared to the A MAY 97 group. In the V21 combination group, 4 out of 5 pigs were protected and viraemia was significantly reduced compared to the monovalent V21 groups. V7 vaccine groups were not protected. The neutralising antibody response was below the detection limit in all groups on the challenge day, showing a poor correlation with protection. There was no evidence that the pigs protected from systemic disease had protective antibody responses sooner than other pigs in the study, implying other immune mechanisms might play a role in protecting these animals. FMDV was detected in the nasal and oral swab samples between 1 and 6 dpc. Viral loads were lower in the nasal swab samples from the V21 combination group than the other groups, but there was no difference in the oral swab samples. Since all unvaccinated controls were euthanised by 6-day post-challenge for ethical reasons, the ‘area under the curve (AUC)' method was used to compare the viraemia and virus excretion in different groups. We recommend that for the A/Asia/SEA97 variants, a combination vaccine with A Malaysia 97 and A22 Iraq 64 vaccine strains would be ideal compared to monovalent vaccines.